Survey of outpatient sputum cytology: influence of written instructions on sample quality and who benefits from investigation. Issue 1 (March 1992) - Tsang, K W; Bentley, A M; Mann, J S; Belcher, J; Pantin, C F
Abstract : OBJECTIVES–To evaluated quality of outpatient sputum cytology and whether written instructions to patients improve sample quality and to identify variables that predict satisfactory samples. DESIGN–Prospective randomised study. SETTING–Outpatient department of a district general hospital. PATIENTS–224 patients recruited over 18 months whenever their clinicians requested sputum cytology, randomized to receive oral or oral and written advice. INTERVENTIONS–Oral advice from nurse on producing a sputum sample (114 patients); oral advice plus written instructions (110). MAIN MEASURES–Percentages of satisfactory sputum samples and of patients who produced more than one satisfactory sample; clinical or radiological features identified from subsequent review of patients' notes and radiographs associated with satisfactory samples; final diagnosis of bronchial cancer. RESULTS–588 sputum samples were requested and 477 received. Patients in the group receiving additional written instructions produced 75(34%) satisfactory samples and 43(39%) of them one or more sets of satisfactory samples. Corresponding figures for the group receiving only oral advice (80(31%) and 46(40%) respectively)were not significantly different. Logistic regression showed that radiological evidence of collapse or consolidation (p<0.01) and hilar mass (p<0.05) were significant predictors of the production of satisfactory samples. Sputum cytology confirmed the diagnosis in only 9(17%) patients with bronchial carcinoma. CONCLUSIONS–The quality of outpatients' sputum samples was poor and was not improved by written instructions. Sputum cytology should be limited to patients with probable bronchial cancer unsuitable for surgery. IMPLICATIONS–Collection of samples and requests for sputum cytology should be reviewed in other hospitals.